Family support and fall risk among the elderly: Insights from a primary healthcare center in Gresik - Nurhayati, Sitti; Subekti, Ahmad; Andi, Wijaya; Budi, Arie (Program Studi Keperawatan, Politeknik Negeri Subang, 2025)
Background: Falls among the elderly represent a significant public health issue, often leading to severe physical injuries, decreased quality of life, and increased healthcare costs. Purpose: This study aims to investigate the relationship between family support and fall risk among elderly individuals in Gresik. Methods: Utilizing a cross-sectional design, 150 elderly participants were surveyed using structured questionnaires assessing demographic characteristics, family support levels, and fall risk factors. Logistic regression analysis was employed to determine the influence of family support and other variables on fall risk. Results: The findings reveal that family support is significantly associated with fall risk, with high levels of family support reducing the likelihood of falls by 75% (OR = 0.25, 95% CI: 0.12-0.51, p < 0.001). Age was also identified as a significant predictor, with each additional year increasing fall risk by 15% (OR = 1.15, 95% CI: 1.02-1.30, p = 0.020). Gender and living arrangements were not statistically significant predictors. Demographic analysis showed that the majority of participants were aged 60-69 years, predominantly female, and living with family members, emphasizing the potential role of family dynamics in elderly care. Conclusion: This study underscores the importance of family support as a protective factor against falls in elderly populations. Interventions focusing on enhancing family involvement, such as caregiver training and home modifications, are recommended to mitigate fall risk. Future research should explore longitudinal designs and qualitative methods to further elucidate the mechanisms of family support in fall prevention.